INSPIRE: Safety and tolerability of inhaled Yutrepia (treprostinil) in pulmonary arterial hypertension (PAH). (24th August 2022) - Hill, Nicholas S.; Feldman, Jeremy P.; Sahay, Sandeep; Benza, Raymond L.; Preston, Ioana R.; Badesch, David; Frantz, Robert P.; Patel, Savan; Galloway, Ashley; Bull, Todd M.
Abstract: The INSPIRE trial was a Phase 3, open‐label, multicenter trial (LTI‐301) that enrolled patients with pulmonary arterial hypertension (PAH) ≥ 18 years of age who transitioned to Yutrepia from nebulized treprostinil (Transition) or added Yutrepia to prostacyclin naïve patients on ≤2 nonprostacyclin oral therapies. The objectives of the trial were to evaluate the safety and tolerability of Yutrepia (dry‐powder formulation of treprostinil) in patients with PAH. The primary safety measures were the incidence of adverse events (AEs) and serious AEs. Exploratory efficacy measures were also assessed during the trial. Transition patients initiated Yutrepia at a dose comparable to their nebulized treprostinil dose while prostacyclin naïve patients received 26.5‐mcg QID; up‐titration in 26.5‐mcg increments was permitted for both groups. A total of 121 patients were enrolled, of which 29 patients discontinued from the trial, with the most common reason being AEs. Eighty percent of the Transition group and 96% of the prostacyclin naïve group titrated to a dose ≥79.5 mcg QID at Day 360, respectively, with one patient achieving a dose of 212‐mcg QID. The most common AEs were cough, headache, upper respiratory tract infection, dyspnea, dizziness, throat irritation, diarrhea, chest discomfort, fatigue, and nasopharyngitis. Most of these events were considered treatment‐related though mild to moderate in severity and expected for prostacyclin therapy administered by inhalation. In an evaluation of exploratory efficacy measures, patients remained stable or improved over the 1 year of treatment. Yutrepia was found to be a convenient, safe, and well‐tolerated inhaled prostacyclin treatment option for PAH patients.